Development Strategy For The Sabang Area With The Logistics Port Concept In The Malaka Strait - Riono Riono; Satrio Teguh Amandiri; Mufidin Mufidin (Universitas Lambung Mangkurat, 2023)
Sabang area is part of the Republic of Indonesia (NKRI) territory, which passed by shipping lines in the Strait of Malacca. Geographic layout of the strategic area, so it is considered a potential to be developed into a maritime area. In the year of 2000, Sabang set to be a free trade area and free port. But until now, this region did not show significant development. In this paper, Sabang area will be assessed the potential and direction of development using the method of TOWS and two step AHP. The direction of development constructed by logistics support concept and simulated using the method of dynamical systems to get the model of the system. The results obtained that Sabang area is potential for development. Simulation of dynamical systems models provides scenarios in anticipation of situations that may happen in the future by increase tank investment and fuel supply so can fulfill fuel needs. In addition, there are a several trickle effects of this system such as the improvement of region economics, the development of docking facilities and service and awareness of regional security.